2013
DOI: 10.1177/0145721713484593
|View full text |Cite
|
Sign up to set email alerts
|

Synergy to Reduce Emergency Department Visits for Uncontrolled Hyperglycemia

Abstract: Diabetes medication management and survival skills education for uncontrolled diabetes may be safely initiated in the ED, as demonstrated by the multidisciplinary STEP-DC intervention, which effectively enabled glycemic control in this pilot study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…In the context of U.S. health care reform and the formation of medical homes in networks of integrated medical and behavioral health services, EMS is well positioned for identifying and facilitating the access of vulnerable, high‐cost service users to and optimal engagement in health services . The findings call for interventions to promote the coordination and integration of EMS delivery with comprehensive, community‐based health services networks for contributing to goals of improved health outcomes and reduced health care costs . Our findings suggest that for Baltimore, public health intervention is especially indicated for enhancing the medical and self‐management of this frequent EMS‐using population's mental illness, substance abuse, diabetes, asthma, HIV, and other chronic conditions.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the context of U.S. health care reform and the formation of medical homes in networks of integrated medical and behavioral health services, EMS is well positioned for identifying and facilitating the access of vulnerable, high‐cost service users to and optimal engagement in health services . The findings call for interventions to promote the coordination and integration of EMS delivery with comprehensive, community‐based health services networks for contributing to goals of improved health outcomes and reduced health care costs . Our findings suggest that for Baltimore, public health intervention is especially indicated for enhancing the medical and self‐management of this frequent EMS‐using population's mental illness, substance abuse, diabetes, asthma, HIV, and other chronic conditions.…”
Section: Discussionmentioning
confidence: 89%
“…While ED data have greater validity, they are not available on a geographically defined population level and are incomplete in national ED reporting systems. For example, data from the U.S. Substance Abuse and Mental Health Services Administration's Drug Abuse Warning Network are subject to selection bias in the restriction to EDs in select geographic areas and low response rates of participating EDs . Data used in this study included information on EMS transports to over 20 area EDs located within 15 different hospitals…”
Section: Limitationsmentioning
confidence: 99%
“…The preplanned analyses presented in this article were conducted as part of a larger prospective randomized controlled study that enrolled patients to test the efficacy of a 3-component intervention that delivered guideline-based diabetes medication management, support for health system navigation, and survival-skills DSME. 23 The data for the 51 patients randomly assigned to the intervention group in the study are included in this analysis. Therefore, the study design reported in this article is a 1-group pretest–posttest design comparing knowledge and skills between intervention group patients’ baseline ED visit and their 24- to 72-hour post-ED discharge follow-up visit.…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes medications were then initiated and/or modified based on the study’s antihyperglycemic medication algorithm. 23…”
Section: Methodsmentioning
confidence: 99%
“…Inpatient diabetes education is intended to deliver the critical survival skills required for safe self-care during the transition from the hospital to the ambulatory setting (Powers et al, 2015). To address the need for sustainable diabetes survival skills education (DSSE) for use in both inpatient and ambulatory settings, we have developed Diabetes to Go (D2Go), a DSSE program that assesses individual diabetes knowledge gaps and links those gaps to educational content (Lewis, Benda, Nassar, & Magee, 2015;Magee et al, 2013;Magee, Khan, Desale, & Nassar, 2014). D2Go has demonstrated effectiveness when provided to general medicine and surgery inpatients and in outpatient settings when delivered in a research context by a study team (Magee et al, 2013;Magee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%